Drug reaction with eosinophilia and systemic symptoms (DRESS) and multiple organ dysfunction syndrome (MODS): one more reason for a new effective treatment against leishmaniasis. (29th August 2018) - Cuestas, Daniel; Forero, Yency; Galvis, Ingrid; Peñaranda, Elkin; Cortes, Carolina; Motta, Adriana; Mora, Sergio; Pérez, Carlos; Velasquez, Oscar; Puentes, José
Abstract: Introduction: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe drug‐induced reaction associated with eosinophilia and systemic manifestations. Anticonvulsants, sulfonamides, and antivirals are the most related and described drugs in DRESS syndrome. Methods and case: We present a case of severe multiple organ dysfunction syndrome (MODS) with the risk of death associated with DRESS syndrome due to antileishmanial pentavalent antimonial drug and its simultaneous toxicity. Consequently, a comprehensive review of the main clinical problems and comparative discussion of both clinical conditions was made. Discussion: The overlap of DRESS syndrome and antileishmanial pentavalent antimonial drug toxicity can be life‐threatening. Both conditions represent a true clinical, diagnostic, and therapeutic challenge. We exposed specific clinical and laboratory results with rare occurrence. Conclusion: Any physician and dermatologists should keep in mind the broad spectrum of clinical manifestations and laboratory findings associated with the use of pentavalent antimonial drugs. The clinical suspicion, an early diagnosis, and aggressive treatment are essential to prevent complications and death.